A high-performance BaTiO3-grafted-GO-laden poly(ethylene oxide)-based membrane as an electrolyte for all-solid lithium-batteries. (29th July 2016) - Angulakshmi, N.; Kar, Goutam Prasanna; Bose, Suryasarathi; Gowd, E. Bhoje; Thomas, Sabu; Stephan, A. Manuel
Abstract : Nanocomposite polymer membrane comprising poly(ethylene oxide), barium titanate-grafted-graphene oxide and lithium bis(trifluoromethanesulfonyl imide) as an electrolyte for all-solid lithium batteries were prepared by a simple hot-press technique. Abstract : Nanocomposite polymer electrolytes (NCPEs) comprising poly(ethylene oxide) (PEO), barium titanate-grafted-graphene oxide (BaTiO3 - g -GO) and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) were prepared by a simple hot-press technique. An increase of two orders of magnitude in the ionic conductivity was achieved upon incorporation of BaTiO3 - g -GO in the polymeric matrix even at 0 °C. The addition of BaTiO3 - g -GO as a filler has significantly enhanced the thermal stability and mechanical integrity of the membrane. The BaTiO3 - g -GO-laden membrane was found to have better interfacial properties with a lithium metal anode than the filler-free membrane. Charge–discharge studies revealed a stable cycling profile even at 5C-rate and it was found to be superior to those reported earlier.